Protocol for public opinion survey, Ecuador 2025 - Javier Chiliquinga-Amaya; Marco Faytong-Haro; Romina Sánchez; Michela Andrade; Efraín Vásquez; Patricio Alvarez-Muñoz (Frontiers in Political Science)
This observational survey protocol aims to investigate public opinion about security and democracy in Ecuador during the critical period in 2025 and 2026. This study will focus on university students, exploring the relationships between trust in the president, approval of his administration, and support for democracy versus the possibility of moving toward regimes with greater military power. The main objective is to understand how trust in different social groups and institutions, perceptions of security, and gender roles influences these political attitudes. Data will be collected monthly from April 2025 to April 2026 using an online questionnaire administered to a representative sample of higher-education students at Milagro State University (UNEMI). The longitudinal design ensured continuity of the same respondents’ data over time. Statistical analyses, including descriptive statistics, nonparametric tests, and logistic regression models, were used to identify the trends and correlations. This study aims to provide anticipated insights into how security perceptions and gender roles could influence policy support, based on data collected in 2025 and 2026. This study emphasizes the importance of balancing security needs with democratic principles, contributing to a more informed and strategic approach to governance in Ecuador.